The Impact of Dementia on Oral Health and Dental Care, Part 2: Approaching and Planning Treatment. Issue 2 (June 2020) - Geddis-Regan, Andrew; Kerr, Kathryn; Curl, Charlotte
Dementia has been described as the biggest health and social care challenge of this century; its impact on dental care cannot be ignored. Dementia affects cognitive ability and decision making, so it is important that oral healthcare professionals are conversant with current mental capacity legislation and issues that may be raised when treatment planning for patients living with the condition. This second article in the series considers the impact of dementia on dental care provision and covers a range of issues which are relevant to both general and specialist practice. These include assessment of capacity, use of different treatment modalities, such as sedation and general anaesthesia, and the factors that may be relevant when deciding to offer treatment or to refer to a secondary care setting for dental treatment. Advanced care planning is detailed to support general dental practitioners considering the longer-term wishes of their patients with an early diagnosis of dementia.